Crowdfunding in Emerging Markets : Lessons from East African Startups - World Bank Group (World Bank, Washington, DC, 2016)
The purpose of this paper is to capture lessons learned from East African entrepreneurs who were some of crowdfunding’s first adopters. Their experiences can serve as a practical guide for entrepreneurs looking to more effectively utilize crowdfunding across all emerging markets. In order to gather this data, the World Bank conducted interviews with a number of East African technology entrepreneurs who ran crowdfunding campaigns, both successfully and unsuccessfully. The following paper offers six key lessons for entrepreneurs in Africa and other emerging markets as they consider when, why and how to launch a crowdfunding campaign: crowdfunding is much more difficult than most entrepreneurs anticipate and is not for everyone. Opportunity costs abound; business needs should dictate platform choice; payment systems impact platform choice; quality and quantity of contributor networks are key; entrepreneurs should tap into complementary resources and organizations to increase their likelihood of success; and crowdfunding can have non-monetary benefits.